Pelatihan dan Sosialisasi Keselamatan dan Kesehatan Kerja (K3) di PT PLN (Persero) - Fardinal Fardinal; Desmarita Leni; Elvis Adril (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Training and socialization of Occupational Safety and Health at PT. PLN (Persero) Teluk Sirih Generation Implementation Unit UIK SBS Bungus Padang District is a community service from the PKM PNP team. This training aims to provide education to employees of PT. PLN (Persero) Teluk Sirih Generation Implementation Unit, UIK SBS, Bungus District to always use occupational safety and health (K3) in the implementation of work. In the field there are still many workers or employees who do not heed the rules of work safety, such as not using safety shoes, helmets, gloves when needed, masks when needed, and even working at a height above 2 (two) meters must use a Body Harness. Employees' disobedience to K3 to maintain work safety will cause problems such as work accidents that still occur as a lot, because in cultivating the company's K3 rules, starting from the Top Management in the department. K3 culture must be applied properly to maintain work stability in the field by providing education through training and socialization of Occupational Safety and Health at PT. PLN (Persero) Teluk Sirih Generation Implementation Unit UIK SBS Bungus Padang District is expected to provide a clear understanding and good education on the understanding of K3 in the industrial world, especially PT. PLN. The method applied to this service provides training and socialization to staff, employees and stake holders of PT. PLN and aims to familiarize the 5S Work Attitude culture, as we know Seiri, Seiton, Seiso, Sheiketsu and Shitsuke. This training helped increase the understanding and awareness of the workforce of PT. PLN (Persero) Teluk Sirih Generation Implementation Unit UIK SBS on K3 culture and the use of personal protective equipment (PPE) for workers when doing work. It is hoped that later when the participants work, they will apply K3 to avoid work accidents.